2018
DOI: 10.2196/mhealth.9888
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Apps for Blood Pressure Monitoring: Systematic Search in App Stores and Content Analysis

Abstract: BackgroundUsing a mobile app for self-management could make it easier for patients to get insight into their blood pressure patterns. However, little is known about the availability, quality, and features of mobile apps targeting blood pressure.ObjectiveThe goal of the research was to determine the availability, functionality, and quality of mobile apps that could be used for blood pressure monitoring purposes.MethodsA systematic app search was performed based on the standards for systematic reviews. We search… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 39 publications
(34 reference statements)
4
58
0
1
Order By: Relevance
“…Main services provided by hypertension m-health apps according to a survey of 107 different products (A) and main characteristics of m-health apps used for blood pressure (BP) monitoring according to another survey of 184 applications (B) [redrawn from (52) and (53) by permission].…”
Section: M-healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Main services provided by hypertension m-health apps according to a survey of 107 different products (A) and main characteristics of m-health apps used for blood pressure (BP) monitoring according to another survey of 184 applications (B) [redrawn from (52) and (53) by permission].…”
Section: M-healthmentioning
confidence: 99%
“…A content analysis of apps specifically designed for BP monitoring has been recently published by Jamaladin et al (53). The authors scrutinized 184 apps, of which 104 Android and 80 iOS apps.…”
Section: M-healthmentioning
confidence: 99%
“…Armstrong [ 61 ] came to the same conclusion with a similar study and suggested government regulation for health data processing. Tabi et al [ 62 ] and Jamaladin et al [ 63 ] also criticized the lack of clarity of conventional app stores and emphasized the need for professional health app stores and medical doctors’ recommendation to their patients. Becker et al [ 64 ] agreed with Huckvale et al [ 60 ] and Armstrong [ 61 ] because most health apps are not certified as a medical device, which means that their data protection terms are, in most cases, not supervised by a government agency.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of data export will allow users to share health reports with their health care providers. Automated data entry can provide greater efficiency in inputting data to the app system while streamlining the user’s experience [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%